Vanini : un poème oublié de Hölderlin - Jacky C.-J. Paul (Recherches Germaniques)
For nearly a century the Ode to Vanini remained unpublished and is still largely ignored in anthologies and research. This article strives to underline the central meaning of the poem for Hölderlin’s work. Indeed, an in-depth reading shows that in this ode and in the conception of nature outlined here—closely related to that of the “despiser of God”—a major and recurring key-theme is emerging which identifies Hölderlin as a militant poet, as an advocate of a “natural philosophy” that requires a radical reassessment of values and contains a message harmful to both the church and the state. A commitment to which he remained faithful all his life. Because, according to certain testimonials little researched so far that invalidate the thesis of Hölderlin’s madness, this “freest spirit” remained a fighter for the “idea of humanity” and the coming of a “new era” until the end of his life.